FEATURES OF MANAGEMENT OF OPERATIONAL ACTIVITIES OF RESTAURANT ENTERPRISES - Kucher, M. M.; Stebliuk, N. F.; Haponenko, S. O.; RazinkovaМ. Yu.; Papsuy, K. O. (Systems and Technologies, 2024)
The article reveals the essence of managing the operational activities of a restaurant business enterprise. The functions of production management at the restaurant business enterprise were considered. The condition and evaluation of the operational efficiency of the restaurant enterprise was analyzed. The main indicators characterizing the production capacity of the operating system at the enterprises of the restaurant industry were established. Indicators that increase the efficiency of the use of production facilities and indicators that characterize the organizational and technical level of production are systematized. Production efficiency indicators were formed into general groups. On the basis of the research, it was found that different both foreign and domestic scientists form certain groups of indicators in their scientific research. It has been proven that operational management requires measurement indicators of such factors as: product quality; innovations; costs; speed of processes; flexibility. The main factors affecting the level of satisfaction of the needs of consumers of restaurant products are considered. The directions for improving the features and a comprehensive approach to the effectiveness of management of the operational activities of the restaurant business have been defined and substantiated. On the basis of this study, it was determined that it is appropriate to accept the profitability of the enterprise’s operational activity as the largest generalizing indicator of the efficiency of the enterprise’s operational activity. The essence of managing the operational activities of a restaurant is to ensure the effective functioning of all aspects of the business related to its daily activities. The main aspects of this management include: processes and operations; product and service quality; HR; financial management; risk and security management; strategic planning and business development. These aspects help to ensure efficient and stable operation of the restaurant, ensuring that customer needs are met, costs are optimized and business goals are achieved.